Memertimbangkan Hermeneutik ala Naṣr Ḥāmid Abū Zayd dalam Studi al-Qur’ān Kontemporer - Iqbal Hasanuddin (Refleksi: Jurnal Kajian Agama dan Filsafat, 2013)
This article states that an approach of Western philosophy in understanding the Qur’ān contextually can be performed to grasp meaning which is much suitable with today condition and in a place we live (here). In this relation, hermeneutic is one of the approaches of Western philosophy used by several contemporary Muslim scholars such as Fazlur Rahman,Mohammad Arkoun, and Naṣr Ḥāmid Abū Zayd. This writing also wants to show a model of reading by Naṣr Ḥāmid Abū Zayd as an example that philosophical approach is used to interpret the Qur’ān.DOI: 10.15408/ref.v13i4.913